Anionic Bipyridyl Ligands for Applications in Metallasupramolecular Chemistry. Issue 19 (15th April 2014) - Pascu, Mirela; Marmier, Mathieu; Schouwey, Clément; Scopelliti, Rosario; Holstein, Julian J.; Bricogne, Gérard; Severin, Kay
Abstract Invited for the cover of this issue is the group of Kay Severin at the EPFL in Switzerland (a picture of the campus is shown above; photo: Alain Herzog, EPFL) and collaborators from Global Phasing in Cambridge. The image refers to the (chemical) advantage of being negative. Read the full text of the article at 10.1002/chem.201400285.